(untitled) (CIPEEX, 2026)
This academic paper examines the evolution and interconnection of the main global and national initiatives to combat climate change and promote sustainable development. It analyzes the United Nations Conference on Environment and Development (ECO-92), which enshrined the concept of sustainable development and established the United Nations Framework Convention on Climate Change (UNFCCC). It then addresses the Kyoto Protocol, with its binding emission reduction commitments for industrialized countries and its flexibility mechanisms. Finally, it explores the 2030 Agenda for Sustainable Development, with its 17 Sustainable Development Goals (SDGs), and the Paris Agreement, which established a universal regime of Nationally Determined Contributions (NDCs). Brazil’s National Policy on Climate Change (PNMC) is presented as an example of national legislation aligned with these global efforts. The paper highlights the progression of climate governance, the importance of international cooperation, the urgent need for emission reductions, and the integration of mitigation, adaptation, finance, and technology dimensions for a sustainable future.